Curcumin inhibits migration and invasion of non-small cell lung cancer cells through up-regulation of miR-206 and suppression of PI3K/AKT/mTOR signaling pathway - Wang Naizhi; Feng Tao; Liu Xiaona; Liu Qin (Acta Pharmaceutica)
Curcumin has been proved to inhibit cell proliferation and induce cell apoptosis in non-small cell lung cancer (NSCLC). However, little is known about antimetastatic effects and molecular mechanisms of curcumin in NSCLC. In this study, we investigated the involvement of miR-206 in curcumin’s anti-invasion and anti-migration in NSCLC. Cell proliferation was determined by MTT assay. Cell migration and invasion were analyzed by wound healing assay and transwell assay. MiRNA-206 expression was detected by real-time PCR. Western blot was used to detect the protein expression of PI3K/AKT/mTOR signaling pathway. Curcumin significantly inhibited migration and invasion in A549 cells, accompanied by significantly elevated miR-206 expression. Overexpression of miR-206 could inhibit migration and invasion of A549 cells, but it could also significantly decrease the phosphorylation levels of mTOR and AKT. The inhibition of miR-206 promoted cell migration, invasion and increased the phosphorylation level of mTOR and AKT. Furthermore, miR-206 mimics improved the inhibitory effects of curcumin on cell migration, invasion and the phosphorylation level of mTOR and AKT in A549 cells. On the contrary, MiR-206 inhibitors reversed the inhibitory effects of curcumin on cell migration, invasion and the phosphorylation level of mTOR and AKT. In conclusion, curcumin inhibited cell invasion and migration in NSCLC by elevating the expression of miR-206 which further suppressed the activation of the PI3K/AKT/mTOR pathway.